EFFECT OF REPEATED CROPPING ON SEED QUALITY INDICATORS OF MUSHROOM AND SOYBEAN CROPS (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2024)
This article examines the effect of mung bean and soybean crops grown as a secondary crop on seed quality indicators. The study analyzed the growth ability of seeds, germination, productivity, and phytopathological status of both types of crops. The work was aimed at determining the beneficial properties of transplanted mung bean and soybean crops, the effect of soil fertility, and changes in climatic conditions on seed quality indicators. As a result, changes in the seed quality indicators of cotton varieties were analyzed and recommendations were given for improving agricultural practices.